Participatory surveillance on influenza as a tool for health promotion - Mexia, Ricardo (2018)
“Conventional” surveillance, usually through sentinel networks or statutory notification systems, can be supplemented by participatory surveillance. Gripenet is an important participatory surveillance tool used in Portugal for influenza surveillance. The platform gathers symptom reports from citizens across the country to calculate ILI (Influenza Like Illness) incidence. While gathering data to perform surveillance is the main focus, the tool is also used for health literacy and health promotion, increasing awareness for several health topics. Gripenet is part of a European consortium including 11 countries and there is still a lot of room to reach other countries and eventually evolve towards surveillance of other diseases or conditions. Description of the problem: The platform is available throughout the year, but only active during influenza season. During that time, a newsletter is sent every week, including the link to provide the symptoms for the surveillance platform, as well as news and recommendations to improve health knowledge, attitude and behaviour. Content is published in the website and also shared in social media (Facebook and Twitter). Results: A total of 26 posts were created and 16 newsletters were issued. In the last registered week, 4404 e-mails were sent, and 1738 users were recorded as active. Facebook reached 301 in the most relevant publication and 63 in the least relevant. Resources allocated are very limited (basic website management and content production) and can reach a significant population, with science based information. Lessons: At a time when misinformation abounds, providing relevant and science based information to the public is paramount. Increasing the reach of the participatory surveillance tool and in the meantime enabling more social media impact is certainly a step in that direction, using limited resources.